2019
DOI: 10.14814/phy2.14298
|View full text |Cite
|
Sign up to set email alerts
|

Achilles tendon shear wave speed tracks the dynamic modulation of standing balance

Abstract: Standing balance performance is often characterized by sway, as measured via fluctuations of the center of pressure (COP) under the feet. For example, COP metrics can effectively delineate changes in balance under altered sensory conditions. However, COP is a global metric of whole‐body dynamics and thus does not necessarily lend insight into the underlying musculotendon control. We have previously shown that shear wave tensiometers can track wave speeds in tendon as a surrogate measure of the load transmitted… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 33 publications
1
4
0
Order By: Relevance
“…The shear wave tensiometers are wearable and noninvasive, thus also providing opportunities for their application outside of the traditional motion capture space 46 . Of note, we have not observed a change in kinematics or kinetics due to wearing the shear wave tensiometer (Figure ) and a previous study showed no significant change in postural sway due to the tapping device 47 . While the research presented here focused on the use of tensiometry to evaluate triceps surae behavior, tensiometery has successfully been used on the patellar tendon in children 26 and may be able to measure hamstring loading as well 16 .…”
Section: Discussionsupporting
confidence: 41%
See 1 more Smart Citation
“…The shear wave tensiometers are wearable and noninvasive, thus also providing opportunities for their application outside of the traditional motion capture space 46 . Of note, we have not observed a change in kinematics or kinetics due to wearing the shear wave tensiometer (Figure ) and a previous study showed no significant change in postural sway due to the tapping device 47 . While the research presented here focused on the use of tensiometry to evaluate triceps surae behavior, tensiometery has successfully been used on the patellar tendon in children 26 and may be able to measure hamstring loading as well 16 .…”
Section: Discussionsupporting
confidence: 41%
“… 46 Of note, we have not observed a change in kinematics or kinetics due to wearing the shear wave tensiometer (Figure S1 ) and a previous study showed no significant change in postural sway due to the tapping device. 47 While the research presented here focused on the use of tensiometry to evaluate triceps surae behavior, tensiometery has successfully been used on the patellar tendon in children 26 and may be able to measure hamstring loading as well. 16 These tendons could be particularly pertinent to study given the high incidence of interventions at these tendons for children with CP walking in crouch gait (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…Because muscle forces are difficult to measure in vivo, [45][46][47] and EMG measurements provide a poor proxy for muscle force production, 48 musculoskeletal modeling has emerged as a popular method to estimate internal muscle forces. [49][50][51][52] However, musculoskeletal models to explore muscle force patterns in the context of knee-related pathologies have remained limited, mostly due to the computational burden required to describe the inherent variability within clinical populations.…”
Section: Discussionmentioning
confidence: 99%
“…Direct measurement of muscle or tendon forces in vivo has historically been possible only under special circumstances [124][125][126][127][128][129]. However, researchers have recently developed a novel shear wave tensiometer to measure tendon forces in vivo during human movement [130,131]. These measurements are likely to become the gold standard for validating muscle force predictions generated by computational neuromusculoskeletal models.…”
Section: Validation Is Often Weakmentioning
confidence: 99%
“…In other cases, imaging methods provide novel in vivo measurements that could improve estimation of model parameter values using optimization methods. For example, tendon forces measured in vivo by shear wave tensiometry [130,131] could be employed as additional constraints when personalizing muscle-tendon model parameter values using EMG, kinematic, and kinetic data.…”
Section: Enhanced Model Personalizationmentioning
confidence: 99%